Astragaloside prevents BDL-induced liver fibrosis through inhibition of notch signaling activation. (1st July 2015) - Yongping, Mu; Zhang, Xiao; Xuewei, Li; Fan, Weiwei; Chen, Jiamei; Zhang, Hua; Chen, Gaofeng; Liu, Chenghai; Liu, Ping
Abstract: Ethnopharmacological relevance: Huangqi decoction was first described in Prescriptions of the Bureau of Taiping People׳s Welfare Pharmacy in the Song Dynasty (AD1078). It consists of Radix Astragali ( Astragalus membranceus (Fisch.) Bge. Root, Huangqi) and Radix Glycyrrhizae ( Glycyrrhiza uralensis Fisch., root and rhizome, Gancao), and it is an effective recipe that is usually used to treat consumptive disease and chronic liver diseases. Astragaloside (AS) is a main component of Radix Astragali had an effect similar to the Huangqi decoction on hepatic fibrosis. Aim of the study: Cholestasis is associated with a number of chronic liver diseases and Notch signaling has been demonstrated to be involved in ductular reaction. Previous studies have shown that AS can prevent the progression of cholestatic liver fibrosis, however, whether AS affects the Notch signaling pathway is unclear. Materials and methods: Cholestatic liver fibrosis was established by common bile duct ligation (BDL) in rats. At first weekend, the rats were randomly divided into a model group (BDL), an AS group, and a Sorafenib positive control group (SORA) and treated for 3 weeks. Bile duct proliferation and liver fibrosis were determined by tissue staining. Activation of the Notch signaling pathway was evaluated by analyzing expressions of Notch-1, -2, -3, -4, Jagged 1 (JAG1), Delta-like (DLL)-1, -3, -4, Hes1, Numb and RBP-Jκ. Activation of the Wnt signaling pathway was evaluated by analyzing expressions of Wnt-4, -5a, -5b, Frizzled (Fzd)-2, -3, -6 and β-catenin. Results: (1) Compared with the BDL group, AS significantly reduced the deposition of collagen and the Hyp content of liver tissue and inhibited the activation of HSCs. In addition, AS significantly decreased the protein and mRNA expressions of TGF-β1 and α-SMA. In contrast, AS significantly enhanced expression of the Smad 7 protein. AS also reduced biliary epithelial cell proliferation, and reduced the mRNA and protein expressions of CK7, CK8, CK18, CK19, OV6, Sox9 and EpCAM. (2) The mRNA and protein expressions of Notch-2, -3, -4 and JAG1 were significantly reduced in the AS compared to the BDL group. In contrast, the mRNA and protein level of Numb was clearly enhanced after AS treatment. Conclusion: AS may prevent biliary liver fibrosis via inhibition of the Notch signaling pathway, thereby inhibiting the abnormal proliferation of biliary epithelial cells. Results indicate that AS may be a potential therapeutic drug for cholestatic liver disease. Graphical abstract: